Durum Wheat Products - Recent Advances - Sissons, Mike (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint details some of the latest developments and the science of durum wheat products outlining the latest research in durum milling innovations, role of durum wheat oil and wheat germ in product stability, available rheological methods to assess semolina, role of processing variables on pasta quality and drying behavior of bulgur. The impact of functional food design on human health and some examples where pasta glycaemic index has been surveyed and products made using waste streams, such as brown algae, tiger nut flour, carrot waste, and other approached to new durum product design such as high amylose durum wheat and soft durum wheat.